Al-Qiyādah Al-Maḥbūbah: A Love-Based Leadership Model for Improving the Performance of Islamic Educational Organisations in the Digital Age - Fawaid Zaini; Zainul Mustafa; Isah Munfarida; Mar’atul Azizah (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2026)
Digital transformation has introduced new challenges for Islamic educational organizations, particularly in balancing organizational effectiveness with the preservation of humanistic and spiritual values. This study aims to construct Al-Qiyādah Al-Maḥbūbah as a love-based leadership model for enhancing the performance of Islamic educational organizations in the digital era. The research employed a qualitative approach using library research and content analysis methods. The data sources consisted of scholarly literature on Islamic leadership, spiritual leadership, servant leadership, compassionate leadership, and digital leadership. Data were analyzed through an interactive model involving data condensation, data display, and conclusion drawing. The findings reveal that Al-Qiyādah Al-Maḥbūbah is built upon three main pillars: Mahabbah Leadership, Rahmah Organizational Culture, and Khidmah-Oriented Leadership. Its implementation in the digital era is supported by three strategic approaches, namely Digital Humanization Strategy, Collaborative Empowerment Strategy, and Digital Spiritual Engagement Strategy. The model contributes to improving work motivation, organizational commitment, employee loyalty, collaborative organizational culture, and the sustainable competitiveness of Islamic educational institutions. This study offers a novel conceptual framework of love-based leadership that integrates Islamic values, humanistic approaches, and digital transformation into a comprehensive leadership model.